2021
DOI: 10.1016/j.physletb.2021.136546
|View full text |Cite
|
Sign up to set email alerts
|

Pre-burst neutrinos of gamma-ray bursters accompanied by high-energy photons

Abstract: Previous researches on high-energy neutrino events from gamma-ray bursters (GRBs) suggest a neutrino speed variation v(E) = c(1 ± E/E ν LV ) with E ν LV = (6.4 ± 1.5) × 10 17 GeV, together with an intrinsic time difference ∆t in = (−2.8 ± 0.7) × 10 2 s, which means that high-energy neutrinos come out about 300 s earlier than low-energy photons in the source reference system. Considering the possibility that pre-bursts of neutrinos may be accompanied by high-energy photons, in this work we search for high-energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Such an energy scale is consistent with various time-of-flight constraints, available today, from MeV neutrinos of supernova 1987A [38] and that from higher-energy neutrinos registered at IceCube, e.g., [39]; it is also compatible with the constraints [40][41][42] from recent multimessenger observations of blazar TXS 0506+056 coincident with ∼ 290 TeV track-like neutrino event [43]. We mention in passing that a light speed variation of v(E) = 1 − E/E γ LV with E γ LV 3.60 × 10 17 GeV has also been suggested from time-of-flight studies on the energetic radiation from GRBs [8,[12][13][14][15][16] and from flares of active galactic nuclei [44]. This latter LV scale is not the same as the LV scale of neutrinos (3.2) but of the same order of magnitude.…”
Section: Speed Variation In Icecube Grb Neutrinossupporting
confidence: 88%
See 2 more Smart Citations
“…Such an energy scale is consistent with various time-of-flight constraints, available today, from MeV neutrinos of supernova 1987A [38] and that from higher-energy neutrinos registered at IceCube, e.g., [39]; it is also compatible with the constraints [40][41][42] from recent multimessenger observations of blazar TXS 0506+056 coincident with ∼ 290 TeV track-like neutrino event [43]. We mention in passing that a light speed variation of v(E) = 1 − E/E γ LV with E γ LV 3.60 × 10 17 GeV has also been suggested from time-of-flight studies on the energetic radiation from GRBs [8,[12][13][14][15][16] and from flares of active galactic nuclei [44]. This latter LV scale is not the same as the LV scale of neutrinos (3.2) but of the same order of magnitude.…”
Section: Speed Variation In Icecube Grb Neutrinossupporting
confidence: 88%
“…Recent studies [11][12][13][14][15] of events in the (near-)TeV-PeV range suggest a linearly energy dependent speed variation of neutrinos through their associations with gamma-ray bursts (GRBs). Analyses lead to a Lorentz violation scale of ∼ 6 × 10 17 GeV, comparable with that determined from GRB photons [16][17][18][19][20][21][22][23]. More intriguingly, it is proposed [13] that either neutrinos or antineutrinos travel faster than the constant light speed c, 1 whereas the other ones go slower than unity.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…anti-neutrinos, this conjecture needs more research in support. Similar to the study of photons, the neutrino research also involves the effects of inherent time delay, and some research found that neutrinos are emitted earlier than GRB photons [107][108][109]. Ref.…”
Section: Gamma-ray Burstsmentioning
confidence: 99%
“…Ref. [109] pointed out that there is a pre-burst stage, which emits neutrinos together with high-energy photons, and this pre-burst stage is within a time interval of about 140∼820 s before the low-energy photon burst of a GRB. Currently, the data of neutrinos are still relatively lacking, and there are prospects for development of LV research using neutrinos.…”
Section: Gamma-ray Burstsmentioning
confidence: 99%